Strategy for Developing the Sharia Business Management Study Program with the Canvas Business Model Approach - Siregar, Rizal Ma'ruf Amidy; Muhammad, Samsuddin; Cahyani, Utari Evy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to benchmark the Sharia Business Management Study Program (MBS Study Program) of the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University (UIN Syahada), accredited as Excellent by LAMEMBA. The approach includes canvas business model analysis and SWOT-based strategy formulation. The results of the study show that the canvas business model of the MBS Study Program consists of nine main blocks, including customer segments, value propositions, channels, customer relationships, revenue sources, key resources, key activities, key partnerships, and cost structures. The strategy formulation produces eight main strategies: diversifying funding sources through research and training collaborations, optimizing digital technology, and innovating educational services.Â